1999
DOI: 10.1002/(sici)1099-1085(19990228)13:3<371::aid-hyp744>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

A nine-year study of the macroinvertebrate fauna of a chalk stream

Abstract: Abstract:The macroinvertebrate fauna of a 50 m site on a partially shaded perennial section of the River Lambourn in Berkshire was studied intensively between 1971 and 1979. This period included a minor drought in 1973 and a major drought in 1976.A quantitative sampling programme for macroinvertebrates was undertaken on each of ®ve distinct biotopes (Berula, Callitriche, Ranunculus, gravel and silt). Each one was sampled in March, June, September and December of 1971 and thereafter in June and December from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 21 publications
3
33
0
1
Order By: Relevance
“…Therefore, we believe that the seasonal dynamics of macroinvertebrate number of taxa in the Pas river basin is primarily driven by the temporal segregation of taxa in relation Macroinvertebrate abundance increased downstream and was almost four times higher in the low flow period (summer) compared to the high one (winter), what is consistent with our second prediction. Similar spatial and temporal patterns have been reported for macroinvertebrate communities of other Atlantic rivers from northern Spain (Riaño et al, 1993;Basaguren et al, 1996;Otermin et al, 2002) and England (Wright & Symes, 1999). Both Riaño et al (1993) and Basaguren et al (1996) suggested that macroinvertebrate abundance is lower in headwaters due to higher hydraulic stress, which can reduce macroinvertebrate food resources such as periphytic biomass (Clausen & Biggs, 1997;Izaguirre & Elosegui, 2005) and the concentration of organic matter (Giller & Malmqvist, 1997).…”
Section: Macroinvertebrate Diversity and Abundance Patternssupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, we believe that the seasonal dynamics of macroinvertebrate number of taxa in the Pas river basin is primarily driven by the temporal segregation of taxa in relation Macroinvertebrate abundance increased downstream and was almost four times higher in the low flow period (summer) compared to the high one (winter), what is consistent with our second prediction. Similar spatial and temporal patterns have been reported for macroinvertebrate communities of other Atlantic rivers from northern Spain (Riaño et al, 1993;Basaguren et al, 1996;Otermin et al, 2002) and England (Wright & Symes, 1999). Both Riaño et al (1993) and Basaguren et al (1996) suggested that macroinvertebrate abundance is lower in headwaters due to higher hydraulic stress, which can reduce macroinvertebrate food resources such as periphytic biomass (Clausen & Biggs, 1997;Izaguirre & Elosegui, 2005) and the concentration of organic matter (Giller & Malmqvist, 1997).…”
Section: Macroinvertebrate Diversity and Abundance Patternssupporting
confidence: 61%
“…Many studies of temperate Atlantic rivers have focused on the effects of unpredictable hydrological disturbances on macroinvertebrate communities (Riaño et al, 1993;Basaguren et al, 1996;Feminella, 1996), but few have reported macroinvertebrate community changes in relation to hydrological predictability during an average hydrological year. However, Wright & Symes (1999), after 10 years of study in the Lambourn River (UK), described higher macroinvertebrate density during the average summer as a consequence of an increase in lentic taxa (e.g. Chironomidae), which were replaced by more reophilic macroinvertebrate families (e.g.…”
mentioning
confidence: 99%
“…Another study of the macroinvertebrate fauna of the River Lambourn during the extreme drought of 1976 found no evidence of loss of family richness but unusually high densities for some families, with rapid recovery at an unpolluted perennial site following drought termination (Wright and Symes, 1999). However, the recovery of invertebrate communities from much longer droughts is poorly understood and confounded by anthropogenic modifications to habitat and river flow (Bond et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As the dry season progresses and water flow is even more reduced, habitat conditions become harsher (Gasith & Resh, 1999), transport of OM (detritus, leaves and plant material) and fine sediments declines and high quantities of OM are stored in pools (Cuffney & Wallace, 1989;Boulton & Lake, 1992;Wright & Symes, 1999). In addition, conductivity and water temperature rise, and low oxygen levels lead to facultative aerobic and anaerobic respiration.…”
Section: Discussionmentioning
confidence: 99%